2002
DOI: 10.1055/s-2002-33193
|View full text |Cite
|
Sign up to set email alerts
|

H2-Histamine Antagonist (Famotidine) Induced Adverse CNS Reactions with Long-Standing Secondary Mania and Epileptic Seizures

Abstract: We report on the case of a 65-year-old female who was treated for one week with famotidine, a reversible H(2)-histamine antagonist, due to gastric pain. Shortly after treatment began, she presented manic symptoms and developed two generalized seizures, after which famotidine was discontinued. Manic symptoms were present for three months; intermittent treatment with both carbamazepine and antipsychotic medication was necessary before her mental status was completely restored. While cimetidine and ranitidine are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Similar findings were reported in mice after administration of cimetidine; systemic administration of large doses resulted in tonic seizures (Amabeoku and Chikuni, 1993), whereas intracerebral administration produced both clonic and tonic seizures (Shimokawa et al, 1996). Even in humans, the H 2 antagonist famotidine has been reported a induce tonic-clonic seizures (von Einsiedel et al, 2002). Speculation has pointed to a role for GABAergic mechanisms (either directly or indirectly) in H 2 antagonist-induced seizures, but this has not been substantiated.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similar findings were reported in mice after administration of cimetidine; systemic administration of large doses resulted in tonic seizures (Amabeoku and Chikuni, 1993), whereas intracerebral administration produced both clonic and tonic seizures (Shimokawa et al, 1996). Even in humans, the H 2 antagonist famotidine has been reported a induce tonic-clonic seizures (von Einsiedel et al, 2002). Speculation has pointed to a role for GABAergic mechanisms (either directly or indirectly) in H 2 antagonist-induced seizures, but this has not been substantiated.…”
Section: Introductionmentioning
confidence: 72%
“…Several studies have reported the appearance of seizures after systemic or central administration of H 2 antagonists (Shimokawa et al, 1996;Gerald and Richter, 1976;Amabeoku and Chikuni, 1993;von Einsiedel et al, 2002). Gerald and Richter reported that systemic and intraventricular administration of the H 2 antagonist metiamide in mice increased the risk of pentylenetetrazol-induced tonic and clonic seizures, respectively (Gerald and Richter, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Os efeitos cardíacos dos antagonistas H 2 só são detectados em indivíduos em estado de choque (CHRUSCH et al, 1999), não havendo evidências de estímulo arritmogênico (UPRICHARD & HARRON, 1990) nem de alteração na pressão sanguínea em Ciência Rural, v.40, n.2, fev, 2010. pacientes saudáveis (MCCORD et al, 2006). Porém, há relatos de desenvolvimento de alterações em sistema nervoso central de seres humanos, como letargia, desorientação, sonolência e confusão, principalmente nos idosos ou em indivíduos com função renal diminuída (SLUGG et al, 1992;EINSIEDEL et al, 2002).…”
Section: Resultsunclassified
“…Famotidine is a histamine receptor antagonist with high selectivity for histamine 2 (H2) receptors. It has been reported to be associated with several unexpected central nervous system (CNS) effects such as delirium, mania, and seizures [10]. Delirium associated with famotidine has been reported in several cases, possibly associated with central anticholinergic effects [11].…”
Section: Discussionmentioning
confidence: 99%